Testing for Hereditary Breast Cancer: Panel or Targeted Testing? Experience from a Clinical Cancer Genetics Practice. Issue 4 (5th December 2014) - Doherty, Jennifer; Bonadies, Danielle C.; Matloff, Ellen T.
Abstract: Approaches to hereditary breast cancer testing are shifting as multi‐gene panels become more widely available. This paper describes our center's experience and outcomes of a 6‐gene panel test as a first‐tier approach in patients who were candidates for BRCA testing. Between July and December 2013, a 6‐gene panel test was ordered for patients meeting criteria for BRCA testing. A retrospective review detailed the mutation and variant of uncertain significance (VUS) rates for the genes analyzed. The mutation rate was 5.2 % ( n  = 7) and the VUS rate was 6.7 % ( n  = 9). A subsequent review determined the number of BRCA‐negative patients who would have been offered additional single gene testing had BRCA, only, been their first‐tier test. Applying consensus criteria revealed 7.1 % ( n  = 9) cases that met criteria for additional testing. Pedigree analysis by a certified genetic counselor revealed 26.8 % ( n  = 34) cases that would have been offered additional testing based on personal and/or family history. Our results suggest that this panel may be warranted as a first‐tier test for a small subset of patients, but likely represents over testing for the majority of patients who are candidates for BRCA testing. The genes selected for panels, the extra costs per patient and the chance of VUS must be considered before we uniformly switch from BRCA to full panel testing on all patients.